The Relationship Of Knowledge And Attitude Of Mother’s Breasfeeding With Exclusive Giving (JURNAL PROTEKSI KESEHATAN, 2020)
Breast milk (ASI) is the only food that is the best for babies, because it has themost complete nutritionalcomposition for baby’s growth and development.Methode: this research is analytic using cross sectional approach. The samplingtechnique is by simple random sampling. Data analysis was performed using theChi-Square test at a significance level of p